Desmopressin and bleeding time in patients with cirrhosis. Issue 6506 (16th November 1985) - Burroughs, A K; Matthews, K; Qadiri, M; Thomas, N; Kernoff, P; Tuddenham, E; McIntyre, N
Abstract : Desmopressin acetate 0.3 microgram/kg was given intravenously to nine patients with chronic liver disease and to a further six such patients in a double blind controlled study versus placebo. Desmopressin acetate significantly shortened the bleeding time compared with basal values in both groups and compared with placebo. There was also a significant decrease in partial thromboplastin time (but not prothrombin time) and significant increases in factor VIII and its components, von Willebrand factor and ristocetin cofactor activity, but not in factors VII, IX, X, XI, or XII. Increased fibrinolysis could be blocked by concomitant administration of tranexamic acid. No important side effects were seen. The multimer pattern of von Willebrand factor was studied for the first time in chronic liver disease. It was normal, but after administration of desmopressin acetate the percentage of multimers of higher molecular weight increased significantly. This may be an important mechanism in the shortening of the bleeding time in cirrhosis, as has been shown in uraemia and other conditions after administration of desmopressin acetate. Desmopressin acetate may be useful in correcting defects in primary haemostasis in chronic liver disease.